2003
DOI: 10.1080/09540260310001606719
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis following traumatic brain injury

Abstract: Psychosis is a relatively infrequent but potentially serious and debilitating consequence of traumatic brain injury (TBI), and one about which there is considerable scientific uncertainty and disagreement. There are several substantial clinical, epidemiological, and neurobiological differences between the post-traumatic psychoses and the primary psychotic disorders. The recognition of these differences may facilitate identification and treatment of patients whose psychosis is most appropriately regarded as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 51 publications
1
22
0
1
Order By: Relevance
“…Preliminary studies suggest that psychotic disorders following TBI are characterized by paranoid delusions and auditory hallucinations, with other hallucinatory experiences and negative symptoms being a less frequent component of the symptom profile [54,55]. In line with the current hypothesis on the physiopathology of psychotic disorders, post-traumatic psychosis has been associated with the presence of cognitive disturbance and neuropathological changes in the frontal and temporal lobes.…”
Section: Clinical Features Of Neuropsychiatric Disorders Following Trmentioning
confidence: 77%
“…Preliminary studies suggest that psychotic disorders following TBI are characterized by paranoid delusions and auditory hallucinations, with other hallucinatory experiences and negative symptoms being a less frequent component of the symptom profile [54,55]. In line with the current hypothesis on the physiopathology of psychotic disorders, post-traumatic psychosis has been associated with the presence of cognitive disturbance and neuropathological changes in the frontal and temporal lobes.…”
Section: Clinical Features Of Neuropsychiatric Disorders Following Trmentioning
confidence: 77%
“…Therefore, atypical antipsychotics seem to be more appropriate. The initial doses must be prescribed from one third to half of the usual ones, increasing them gradually and carefully, since these individuals are particularly susceptible to side effects (Arciniegas et al 2003). Well succeeded treatments using risperidone (Schreiber et al 1998) and olanzapine (Arciniegas et al 2003;Warden et al 2006) were reported, as well as the association between risperidone with galantamine (Bennouna et al 2005).…”
Section: Treatmentmentioning
confidence: 99%
“…Case studies (varying between one and nine patients) of atypical antipsychotic agents such as clozapine, risperidone and olanzapine given to TBI patients showed mixed results. [115][116][117] It is evident that more effective treatment modalities are needed in treatment-resistant schizophrenia, or any form of thought disorder, to address the needs of patients who remain substantially symptomatic and disabled even with the use of currently available antipsychotic agents.…”
Section: Psychopharmacological Treatmentmentioning
confidence: 99%